Helix α-3 inter-molecular salt bridges and conformational changes are essential for toxicity of Bacillus thuringiensis 3D-Cry toxin family - Pacheco, Sabino (Sci Rep, 2018)
Bacillus thuringiensis insecticidal Cry toxins break down larval midgut-cells after forming pores. The 3D-structures of Cry4Ba and Cry5Ba revealed a trimeric-oligomer after cleavage of helices α-1 and α-2a, where helix α-3 is extended and made contacts with adjacent monomers. Molecular dynamic simulations of Cry1Ab-oligomer model based on Cry4Ba-coordinates showed that E101 forms a salt-bridge with R99 from neighbor monomer. An additional salt bridge was identified in the trimeric-Cry5Ba, located at the extended helix α-3 in the region corresponding to the α-2b and α-3 loop. Both salt-bridges were analyzed by site directed mutagenesis. Single-point mutations in the Lepidoptera-specific Cry1Ab and Cry1Fa toxins were affected in toxicity, while reversed double-point mutant partially recovered the phenotype, consistent with a critical role of these salt-bridges. The single-point mutations in the salt-bridge at the extended helix α-3 of the nematicidal Cry5Ba were also non-toxic. The incorporation of this additional salt bridge into the nontoxic Cry1Ab-R99E mutant partially restored oligomerization and toxicity, supporting that the loop between α-2b and α-3 forms part of an extended helix α-3 upon oligomerization of Cry1 toxins. Overall, these results highlight the role in toxicity of salt-bridge formation between helices α-3 of adjacent monomers supporting a conformational change in helix α-3.